EDITORIAL - Goh, Pauline Swee Choo; Ratnavadivel, Nagendralingan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Welcome to the end-of-year edition of the Journal of Research, Policy & Practice of Teachers & Teacher Education (JRPPTTE). We are pleased to announce that JRPPTTE has been accepted to be included into Taylor & Francis’ Educational Research Abstracts online (ERA). Educational Research Abstracts Online (ERA) is a comprehensive database comprising fully indexed abstracts which cover the current international research in education. ERA is supported by a fully-flexible search engine, and comprises links to the full-text online versions of articles to over 25 specialist datasets representing all the key areas of educational research. We are very proud to be part of this database.